Involving Victim Population In Environmentally Sustainable Strategies: An Analysis For Post-Conflict Colombia (2018)
Environmental objectives tend to receive a push to the background in post-conflict scenarios. On the other hand, the processes displacement and refugee's relocation in post-conflict countries have been associated with different environmental impacts. Currently, Colombia faces a post-conflict scenario, which brings about relevant socio-environmental challenges: it is a mega-biodiverse country, it has millions of displaced people and is one of the most inequitable country in the world. Since there is a gap in post-conflict studies regarding the exploration of victims' involvement in environmental strategies, this paper aims to analyze victims' willingness to participate (WP) in Land Recovery Strategies (LRS) in post-conflict Colombia. This research (1) describes the socio-economic characteristics of forced-displacement victims from a Caribbean municipality of Colombia; (2) analyzes the victims' WP in hypothetical LRS and their preferred type of participation in the project, (3) identifies the way of grouping victims according their WP. Finally, (4) it analyzes the kind of benefits victims would prefer to receive in exchange for their participation in the LRS. Our results made evident that the majority of the consulted victims are willing to participate in LRS by giving up manual work time or in exchange of local ecological knowledge. We also found that the victims' participation in LRS associates to the age of the respondents, and whether they have benefited from government programs previously.